The Role of FIP-2 (Optineurin) in Regulation of the Chemokines and Kinases - Tarassishin, Leonid; S. Horwitz, Marshall (Journal of Proteomics and Genomics Research, 2014)
FIP-2 is a multifunctional protein which is involved in various cellular processes. Using different approaches we investigated its regulatory activity. The microarray analysis has shown that FIP-2 substantially altered the expression of 75 genes (35+/40-) from different functional groups with maximal presentation in “Signal transduction” and “Transcription regulation”. Real time RT-PCR indicated significant elevation in the transcription of chemokines, particularly IL-8 (CXCL8). Production of IL-8 in HEK293 cells dramatically increased with FIP-2 overexpression. We also demonstrated that FIP-2 induced activation of IL-8 promoter activity through NF-kB binding site. Additionally, we showed that FIP-2 could interact with PAK3 and increase its kinase activity. Overall, we demonstrated the role of FIP-2 in the regulation of chemokines (IL-8, MPIF-1, MCP-1) and kinases (PAK3, ALK).
Keywords: FIP-2 (optineurin); microarray; gene expression; regulation; interleukin-8; p21-activated kinase 3